Changes in body composition, bone metabolism, strength, and skill-specific performance resulting from 16-weeks of HIFT. - Yuri Feito; Wade Hoffstetter; Paul Serafini; Gerald Mangine (PLoS ONE)
High Intensity Functional Training (HIFT) is a training modality, characterized by multimodal exercises performed at high-intensity. Little is known about the training adaptations that occur as a prolonged training program. The purpose of this study was to examine changes in body composition, bone metabolism, strength, and skill-specific performance over 16-weeks of HIFT. Twenty-six recreationally active adult males (n = 9; 34.2 ± 9.1 y; 91.5 ± 17.7 kg; 178.5 ± 5.4 cm) and females (n = 17 = 36.4 ± 7.9 y; 91.5 ± 17.7 kg; 162.9 ± 7.0 cm) completed pre and post training assessments of body composition (Dual-Energy X-Ray Absorptiometry) and performance measures. Performance was assessed using three HIFT workouts (WOD 1-3) to assess strength, skill, and metabolic performance. Aside from the body composition measurements, all assessments were carried out at the local training facility. Training included participation in HIFT a minimum of twice a week for 16-weeks. Repeated measures analysis of variance revealed a significant gender x time interaction in Bone Mineral Content (BMC) (p = 0.027), where improvements favored women (1.0% ± 1.1%, p = 0.004) over men (-0.1% + 0.8%, p = 0.625). Further, region-specific analysis indicated that women (2.5% ± 3.0%, p < 0.005) experienced greater improvements in the trunk compared to men (-0.3% ± 1.8%, p = 0.621), while changes in leg BMC were comparable between women (0.8% ± 1.0%, p < 0.001) and men (0.3% ± 0.6%, p < 0.001). Although no other interactions were observed, significant performance improvements were noted for all participants in WOD 1 (18.3% ± 16.8%), absolute 5RM (14.4% ± 9.7%), relative 5RM (15.4% ± 9.2%), WOD 2 (5.7% ± 6.5%), and WOD 3 (-17.3% ± 14.7%). These data indicate that 16-weeks of HIFT resulted in positive outcomes in strength, metabolic conditioning performance, and body composition.